The needs and preferences of Eastern Canadian sex workers in mitigating occupational health and safety risks through the use of Information and Communication Technologies: A qualitative study - Bernier, Thérèse; Shah, Amika; Ross, Lori E.; Logie, Carmen H.; Seto, Emily (PloS one, 2022)
Sex workers may use Information and Communication Technology (ICT) as a means to mitigate occupational health and safety (OHS) risks by exchanging harm reduction techniques (e.g., screening) on blogs and social media. ICTs can also assist sex workers in creating online communities, where community members can act as each other’s safety check-ins, an additional harm reduction technique. In Canada, there is a paucity of research around ICT usage by sex workers for managing occupational health and safety. The objective of this study was to qualitatively examine the needs and preferences of Canadian sex workers when using ICTs in the delivery of strategies for occupational health and safety. Using a theoretical framework derived from a Social Ecological Model perspective, semi-structured interviews were conducted via phone, with a mixed gender sample (N = 22) of sex workers, between April and July 2020. OHS risks were found to be related to structural determinants, client behaviours, and lack of experience and knowledge when newly entering sex work. Participant accounts revealed a socially cohesive online community; however, sex workers reported difficulties in finding these communities, particularly when entering sex work. Such barriers to supportive communities were attributed to the criminalized, hidden nature of sex work that resulted in the fragmentation of harm reduction techniques across several online platforms, such as blogs, YouTube videos, closed electronic chat groups, and open online sex worker supportive communities. Moreover, these platforms and/or their content could potentially disappear without warning, either due to the platform provider seeking to evade possible prosecution, or because new legislation was introduced banning such content. Recommendations for further research include the co-design with sex workers of an innovative, secure, easily accessible, sex worker-only ICT OHS tool, utilizing a web hosting service located in a country where sex work has been either legalized or decriminalized.